Noninvasive respiratory assistance as aid for respiratory care in neuromuscular disorders - Andrew Graustein; Hugo Carmona; Joshua O. Benditt (Frontiers Media S.A., 2023)
Chronic respiratory failure is a common complication of neuromuscular disease. The use of noninvasive ventilation and mechanically assisted cough can reduce symptoms of hypoventilation, slow lung function decline, improve sleep quality, and in some cases prolong survival in patients with neuromuscular disease. In this article, we review indications for the initiation of noninvasive ventilation and mechanically assisted cough as well as provide recommendations for settings and titration. We discuss the evidence supporting the use of noninvasive ventilation as an adjunct to rehabilitation in patients with neuromuscular disease. Lastly, we review the ethical considerations that are relevant to decisions regarding initiation and cessation of noninvasive ventilation. While noninvasive ventilation and mechanically assisted cough have become standards of care in many forms of neuromuscular disease, most current recommendations are based on expert opinion rather than much-needed data from prospective clinical trials and we emphasize topics requiring future research.